Cytogenetic Investigation of Some Ranunculus L. Species Distributed in Bitlis and its Surroundings - Almazov, Shukurjan; Sancar, Pelin Yılmaz; Kurşat, Murat; Gedik, Osman; Civelek, Semsettin (My University, 2023)
Ranunculus L. genus has 84 species in Turkey, when subspecies and varieties are included in this number, it is represented by a total of 102 taxa. 22 of which are endemic, the endemism rate is 21.5%. Since many members of the genus Ranunculus cannot be distinguished from each other with definite differences, they have been tried to be defined and expressed as species complexes taxonomically. Most of the systematic studies are in the direction of regulating such complexes. It is known that karyological characters are of great importance in the phylogenetic classification of the Ranunculaceae family. In this study, it is aimed to reveal the karyological characteristics of three species which are very similar to each other, in Group A of Ranunculus subgenus of Ranunculus L. in Volume 1 of Flora of Turkey morphologically by using cytogenetic methods. In this context, the karyological characteristics of R. diversifolius Boiss. & Kotschy, R. poluninii Davis and R. crateris Davis species have been determined. R. poluninii and R. crateris species are endemic to our country and are Iran-Turanian element. R. diversifolius species, on the other hand, is distributed in the East of Turkey. It has been determined that all three species whose chromosomal characteristics were examined are diploid and their chromosome numbers are x=8, 2n=16. It has also been determined that these three species, which are morphologically similar to each other, are the same in terms of chromosome number but different in terms of chromosome morphology and each species has its own characteristics. With this study, the chromosomal characteristics of these three species have been determined for the first time by us and have been brought to the literature.
Keywords: Turkey; Ranunculus; Chromosome